2018
DOI: 10.1097/qai.0000000000001574
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Self-Reported Pre-exposure Prophylaxis Interruptions Among HIV-Negative Partners in HIV Serodiscordant Couples in Kenya and Uganda

Abstract: IPV was more likely to be reported at visits when PrEP interruptions were also reported, which may have implications for sustained adherence to PrEP. Within PrEP delivery programs, there may be opportunities to assess individual safety and well-being to bolster adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Indeed, women's desire to preserve their relationship and trust their partner may weigh more in their lives than their risk of acquiring HIV and prevention considerations . Intimate partner violence (IPV) has since been shown to have been associated with non‐adherence . HIV and stigma associated with antiretrovirals were also barriers to product use.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, women's desire to preserve their relationship and trust their partner may weigh more in their lives than their risk of acquiring HIV and prevention considerations . Intimate partner violence (IPV) has since been shown to have been associated with non‐adherence . HIV and stigma associated with antiretrovirals were also barriers to product use.…”
Section: Discussionmentioning
confidence: 99%
“…One concern with this trial, however, is that the long duration between PrEP visits (6 months) and reduced contact with PrEP providers might instead reduce adherence among PrEP users because contact with the health system is needed to stay motivated and/or be supported to continue with good adherence. In addition, there are concerns that participants in the HIVST intervention arms might be at greater risk of experiencing intimate partner violence if, for example, sexual partners find out about HIV-1 status through HIVST [58]. All participants will be carefully screened for incidents of intimate partner violence at each study visit and will be linked to existing services if they seem at risk, as this study team has done in other PrEP and HIVST studies.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have shown that GBV increases HIV acquisition for women [ 5 , 7 10 ], especially for adolescent girls, who are at risk of transactional or forced sex [ 11 13 ]. GBV also undermines HIV prevention and treatment cascades [ 14 – 21 ]. Although findings are mixed, studies indicate that women’s fear of IPV prevents them from attending HIV counselling and testing (HCT) services, and could affect uptake, adherence or early discontinuation of PrEP [ 20 ], while others have found that IPV is associated with poorer ART adherence [ 14 ].…”
Section: Introductionmentioning
confidence: 99%